A Dynamic Allocation Algorithm for Physical Carrier Resource in BBU Pool of Virtualized Wireless Network - Ganqiang Lu; Caixia Liu; Lingshu Li; Quan Yuan (2015 International Conference on Cyber-Enabled Distributed Computing and Knowledge Discovery, 2015)
In order to deal with the rapid growth of mobile data traffic and reduce the infrastructure capital expenditure (CAPEX) and operating expense (OPEX), C-RAN is introduced into wireless access network architecture. C-RAN can implement the separation of baseband processing unit (BBU) and remote radio head (RRH). Baseband processing resources are shared by the centralizing deployment of BBU in data center, while RRH is only as a wireless access point that is responsible for sending and receiving signals. Software Defined Network (SDN) and Network Function Virtualization (NFV), the candidate technologies for future development of wireless access network, can promote the virtualization of wireless access network. In this paper, the dynamic allocation of carrier resource in BBU pool is studied, and a dynamic combination allocation algorithm based on Karnaugh map and enhance genetic algorithm (KMEG) for resource allocation of carrier resource is also presented. The simulation results show that this algorithm can deal with different mobile service request for underlying resource effectively, which can adjust system capacity dynamically on demand and achieve the dynamic share of heterogeneous underlying resources in BBU pool. In addition, this algorithm can improve the receiving rate of VNs compared with the static resource allocation algorithm, which can enhance the utilization rate of underlying resources and spectrum efficiency greatly.